Human neural correlates of emotional well-being (EWB): a preliminary systematic review and meta-analysis of MRI studies based on a recent consensus definition - Luo, Jie; Lay, Celinene M.; Richter, Caroline G.; Turnbull, Adam; Richlan, Fabio; Park, Crystal L.; Hoeft, Fumiko (Frontiers in Human Neuroscience, 2025)
IntroductionEmotional well-being (EWB) is a multifaceted construct essential for human health, conceptualized as an umbrella term for related psychometric concepts such as psychological well-being (PWB), positive mental health, health-related quality of life, thriving, and subjective well-being (SWB). However, varying definitions have prompted calls for a consensus definition. Understanding the neural mechanisms of EWB is crucial for health and intervention efforts, yet findings remain inconsistent in both empirical studies and systematic reviews. The inconsistencies in prior systematic reviews may arise from diverse definitions, an emphasis on task-independent over task-dependent modalities, and biases introduced when statistical analyses are lacking.MethodsTo address these gaps, this study presents the first preliminary systematic review and meta-analysis of the neural correlates of EWB using a consensus definition developed in 2023 by NIH EWB Research Network, which includes five domains: goal pursuit, life satisfaction, positive affect, quality of life, and sense of meaning. Importantly, we used a hypothesis-driven approach to separately examine task-dependent (task-based fMRI; n = 14) and task-independent modalities (resting-state fMRI and structural MRI; n = 7 each), clarifying their distinct and overlapping neural contributions of EWB.ResultsThe left pallidum as a key region associated with task-dependent modality, likely reflecting incentive and rewards processing, while task-independent findings implicate the right superior temporal gyrus (STG) and insula, suggesting roles in social cognition and interoceptive awareness. Across both modalities, frontoparietal regions emerge as shared substrates likely contributing to cognitive control processes central to EWB.ConclusionDespite limited sample sizes, this review provides a preliminary neural framework of EWB, highlighting distinct and shared contributions across modalities and lay an empirical foundation for future large-scale investigations.Systematic review registrationhttps://osf.io/ymtb8/overview